EXPERIMENTAL AND NUMERICAL STUDY FOR FREE VIBRATION ANALYSIS OF SANDWICH PLATES WITH CUTOUT - Emad, Sahar (Journal of Applied Engineering Science, 2025)
In this paper, free vibration assessments of sandwich plates with a square, triangle, and circle cutouts were performed both theoretically and practically. Cutouts are inescapable in structural applications, and their presence significantly affects the structure’s dynamic qualities. A finite element model was created with ANSYS software to investigate the vibration properties of sandwich plates with cutouts. The model’s development takes into account the Shell 292 element, a 12-noded element with six degrees of freedom that may be used to examine various fixed edge configurations. The natural frequencies and mode shapes of the sandwich structure were determined for various edge numbers.